The Effect of Variance Discharge on the Dissolved Salts Concentration in the Euphrates River upper reach, Iraq - Al- Ali, Iman A.; Al- Dabbas, Moutaz A. (Iraqi Journal of Science, 2022)
The Euphrates River Basin in Iraq suffers from climate changes represented by the scarcity of precipitation and the increase in temperatures, which is directly reflected in the discharge rates and the increase in total dissolved solids, and consequently, the increase in the dissolved loads in the river. Four measurement stations (Haditha, Ramadi, Fallujah, and Al-Hindiya) in the upper reach of the Euphrates River were investigated. Available data were analyzed from 1970 to 2020 related to precipitation (mm) and temperatures (°C). The results showed a clear decrease in precipitation rates over the years, while a clear increase in air temperature rates was observed. The discharge rates decreased temporally and spatially downstream as follows: 502, 383.7, 382.1, and 211.8 m³/s in Haditha, Ramadi, Fallujah, and Al-Hindiya, respectively. The average total dissolved solids (ppm) from 2005 to 2020 shows a gradual increase downstream, 698.8, 764.8, 833, and 922.3 ppm. The dissolution load classification curves for 2005 to 2020 show an increase in the downstream dissolved loads of 0.781, 0.786, 0.927, and 0.944 million tons/month in Haditha, Ramadi, Fallujah, and Al-Hindiya, respectively. It reflects the increase in the dissolution process of basin materials cumulatively downstream. It is recommended that careful management of the transmission of pollutants of agricultural and anthropogenic activities outputs into the river without any treatments for the downstream reaches will be required.